2020
DOI: 10.1002/cncy.22254
|View full text |Cite
|
Sign up to set email alerts
|

Does a higher American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI‐RADS) score forecast an increased risk of malignancy? A correlation study of ACR TI‐RADS with FNA cytology in the evaluation of thyroid nodules

Abstract: BackgroundUltrasound has become the initial approach to evaluating thyroid nodules, facilitating the distinction between benign and malignant nodules based on composition, echogenicity, nodule border or margin, shape, the presence of calcifications, and nodule dimensions. The American College of Radiology (ACR) recommended the Thyroid Imaging Reporting and Data System (TI‐RADS) as a classification system to standardize thyroid ultrasound reports and to predict the probability of malignancy in thyroid nodules u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 23 publications
7
51
0
1
Order By: Relevance
“…A good correspondence between radiology and cytology was noted in cases with ACR class 1–2, 90% (62/69) of which belonged to the <TIR3A (Bethesda AUS) group, and only seven nodules were classified as TIR3A, benefitting from a strict follow-up policy ( Table 2 ). These results support an excellent “rule-out” role for the ACR-TIRADS system that would significantly reduce the number of FNAs performed on benign nodules, as previously demonstrated [ 13 , 14 , 15 , 16 , 18 , 21 , 22 , 23 , 24 ]. For these cases, FNAs may be avoided if not strictly indicated by clinical needs, such as symptomatic goiter or therapeutic decompression of upper airways.…”
Section: Discussionsupporting
confidence: 85%
“…A good correspondence between radiology and cytology was noted in cases with ACR class 1–2, 90% (62/69) of which belonged to the <TIR3A (Bethesda AUS) group, and only seven nodules were classified as TIR3A, benefitting from a strict follow-up policy ( Table 2 ). These results support an excellent “rule-out” role for the ACR-TIRADS system that would significantly reduce the number of FNAs performed on benign nodules, as previously demonstrated [ 13 , 14 , 15 , 16 , 18 , 21 , 22 , 23 , 24 ]. For these cases, FNAs may be avoided if not strictly indicated by clinical needs, such as symptomatic goiter or therapeutic decompression of upper airways.…”
Section: Discussionsupporting
confidence: 85%
“…According to Modi et al 2020, the mean nodule size in TIRADS 3 category was 2.9±1.27 cm. 11 The mean nodule size in TIRADS 4 category of our study was 1.9±1.05 cm. According to Modi et al 2020, the mean nodule size for the same category was 2.3±1.29.…”
Section: Discussionmentioning
confidence: 51%
“…According to Modi et al 2020, the mean nodule size for the same category was 2.3±1.29. 11 In TIRADS 5 category of our study the mean nodule size was 0.8 cm. According to Modi et al 2020, the mean nodule size in TIRADS 5 category was 1.7±1.11cm.…”
Section: Discussionmentioning
confidence: 52%
“…All radiologists retrospectively analyzed B-mode ultrasound images and evaluated the following features: composition, echogenicity, shape, margin and echogenic foci based on ACR TI-RADS categories [9]. A recent study showed there were no malignant diagnoses of thyroid in TR2 and TR3 (Bethesda, Category VI) [32]. TR3 is of low malignancy, therefore the cutoff between benign and malignant thyroid nodules was set at TR4 in this study.…”
Section: Analysis By Radiologistsmentioning
confidence: 99%